Genetic variability among Commelina weed species from the states of Paraná and São Paulo, Brazil - Rocha, D. C.; Rodella, R. A. [UNESP]; Marino, C. l. [UNESP]; Martins, D. [UNESP] (Sociedade Brasileira da Ciência das Plantas Daninhas, 2009)
This work aims to carry out a comparative analysis using RAPD molecular markers in four Commelina weed species from the state of Paraná and C. benghalensis populations from the states of Paraná and São Paulo, Brazil. The genomic plant DNA sample was extracted from the leaves, separated, randomly fragmented and amplified by PCR. Random amplified polymorphic DNA fragments (RAPD markers) were analyzed by using POPGENE statistical program. Eighty-five primer sequences were tested but only three were suitable as molecular markers producing 37 DNA polymorphic fragments for comparisons among four Commelina species and 22 polymorphic fragments for comparisons among C. benghalensis populations. The results showed that there were inter-specific and intra-specific genetic variabilities among Commelina plant genera. Genetic diversity analysis between species indicated four mono-specific clusters and it was suggested to keep C. villosa as one species. Regarding the intra-specific genetic variability of C. benghalensis alone, three groups were verified, although there were 13 populations from two geographical areas. However, these clusters do not correspond to the distinct characteristics verified.

O presente trabalho procurou analisar a variabilidade genética, utilizando-se de marcadores RAPD, comparando quatro espécies de Commelina procedentes do Estado do Paraná e entre populações de C. benghalensis procedentes dos Estados do Paraná e São Paulo. Foi amostrado o DNA genômico extraído das folhas, o qual foi separado, fragmentado aleatoriamente e amplificado por PCR. Os fragmentos polimórficos de DNA (marcadores RAPD) foram analisados pelo programa estatístico POPGENE. Oitenta e cinco primers foram testados, mas somente três sequências foram consideradas marcadores moleculares, produzindo 37 bandas de DNA polimórfico para comparação entre as quatro espécies de Commelina e outras 22 para comparação entre as populações de C. benghalensis. Os resultados mostraram que há variabilidade genética inter e intraespecífica nas plantas do gênero Commelina. A análise da diversidade genética entre as espécies indicou quatro agrupamentos monoespecíficos, e isso sugere manter C. villosa como uma espécie. Considerando a variabilidade genética intraespecífica somente de C. benghalensis, apesar das 13 populações provenientes de dois Estados geográficos, três grupos foram identificados. Entretanto, esses agrupamentos não correspondem às características morfológicas distintas observadas.
Variabilidade genética entre espécies de plantas daninhas do gênero Commelina provenientes dos estados do Paraná e São Paulo, Brasil
Keywords: biótipo; Commelinaceae; marcadores moleculares; planta daninha; biotype; Commelinaceae; molecular markers; weeds